Distributed generation installation using particle swarm optimization - L., Y. Wong; Siti Rafidah, Abdul Rahim; Mohd Herwan, Sulaiman; Aliman, Omar (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/